Sustainability of print media in the digital era : a study of selected South African newspapers - Mabasa, Engetani Lucia (My University, 2025)
In the digital age, the print media face numerous challenges. The rise of digital media, particularly new internet-based media, has aided to the downfall of print media. Traditional media, especially newspapers, experience both opportunities and threats from digital media. Owing to these challenges and threats to print media, several newspapers have ceased operations, while others have moved to digital formats. The purpose of this study is to determine the sustainability of print newspapers given the ongoing media digitalisation competition. This research focused on several strategies that media companies could employ to remain sustainable.On the other hand, there is a lack of research in South Africa on how print media companies can remain sustainable despite the many digital obstacles they face. Thus, the purpose of this study is to close this knowledge gap. Moreover, by evaluating strategies adopted by print newspapers to maintain the viability of their media companies in the digital age, the study sought to broaden the body of knowledge on the sustainability of print newspapers in the digital age. Furthermore, outlining some best practices and techniques, the study provided suitable approaches that media managers can use to properly handle and manage their media companies in the digital era. This study employed a qualitative methodology, drawing samples from readers, print media experts, and the practitioners of the selected print newspapers through interview processes. It examined various attempts in which newspapers achieve sustainability in the digital era. This was done using semi-structured interviews. It is important to note that media sustainability in the digital age extends beyond financial sustainability. It should consider its institutional and social sustainability. The findings reveal that, for print media companies to survive in the digital era, they should constantly promote subscriptions, interact with readers, and maintain their credibility and trustworthiness.Theoretically, mediamorphosis proved that print and digital media may coexist; the expansion of one does not always mean that the other would be diminished. This study has been able to further knowledge by outlining strategies for print newspapers to become sustainable in the digital age.
Thesis (Ph.D. (Media Studies)) -- University of Limpopo, 2025
Keywords: Digital era; Mediamorphosis; Newspapers; Print Media; Sustainability; South Africa; Mass media -- Technological innovations; Mass media -- History; South African newspapers -- History; Digital media; Newspaper publishing -- South Africa